An efficient MPS refined technique with adaptive variable-size particles. (October 2022) - Zhang, Kai; Sun, Yi-Jie; Sun, Zhong-Guo; Wang, Feng; Chen, Xiao; Xi, Guang
Highlights: The shape and position of the high-resolution domains were able to dynamically trace the moving/deformable body with mass and momentum conservation. The particle size is not unique but a range for each resolution domains, and the principle of resolution selection between neighboring domains is optimized. New splitting/coalescing criterion is proposed to avoid chain split/coalesce reaction, and to improve the convergence near the multi-resolution boundaries. The AVSP-MPS method sharply reduces the particle number and the computational time. Abstract: For the single-resolution particle method, large computation demand with high accuracy commonly requires enormous number of particles, which becomes greatly time-consuming. The moving particle semi-implicit (MPS) method with variable-size particles (VSP) has been proposed to refine particles in local domain. However, in VSP-MPS method, the refined area is fixed in the calculation, which makes it difficult to precisely capture flow near moving and deformable boundaries. This study develops a MPS method with adaptive variable-size particles model, called AVSP-MPS. In this method, by capturing moving and deformable boundaries, the objective computational domain can be dynamically refined. A new criterion, that splitting and coalescing only happen when the entire particle crosses the refined interface, is proposed to avoid unnecessary chain reactions of particle splitting and coalescing. The stability of the method is therefore improved. The district resolution is not a specific value, but a range in VSP model. An inappropriate selection of resolution range would cause repetitive splitting and coalescing, leading to low efficiency of the computation. In this research, the new maximum and minimum volumes in the region with different resolutions, as an optimized result, are obtained to improve convergence near the multi-resolution boundaries. Several cases as dam break and water entry are verified. The numerical results show that the AVSP-MPS method has an efficient, flexible and stable refinement technique in treating complex flow with large deformation.